Cervical cancer screening uptake and correlates among HIV-infected women: a cross-sectional survey in Côte d’Ivoire, West Africa - Eugene Messou; Didier K Ekouevi; Boris Tchounga; Simon Pierre Boni; Jean Jacques Koffi; Apollinaire G Horo; Aristophane Tanon; Serge-Olivier Koulé; Innocent Adoubi; Antoine Jaquet (BMJ Open)
Objectives Despite the increasing number of interventions aiming to integrate cervical cancer screening into HIV clinics in sub-Saharan Africa, Women living with HIV (WLHIV) still have a high risk of developing cervical cancer. The aim of this study was to estimate the coverage of cervical cancer screening and associated factors among WLHIV in Abidjan, Côte d’Ivoire.Design Cross-sectional survey conducted from May to August 2017.Settings Outpatient setting in the four highest volume urban HIV clinics of government’s or non-governmental organisation’s sector in Côte d’Ivoire.Participants All WLHIV, aged 25–55 years, followed since at least 1 year, selected through a systematic sampling procedure.Intervention A standardised questionnaire administered to each participant by trained healthcare workers.Outcome Cervical cancer screening uptake.Results A total of 1991 WLHIV were included in the study, aged in median 42 years (IQR 37–47), and a median CD4 count (last known) of 563 (378-773) cells/mm3. Among the participants, 1913 (96.1%) had ever heard about cervical cancer, 1444 (72.5%) had been offered cervical cancer screening, mainly in the HIV clinic for 1284 (88.9%), and 1188 reported a personal history of cervical cancer screening for an overall coverage of 59.7% (95% CI 57.6 to 62.0). In multivariable analysis, university level (adjusted OR (aOR) 2.1; 95% CI 1.4 to 3.1, p<0.001), being informed on cervical cancer at the HIV clinic (aOR 1.5; 95% CI 1.1 to 2.0, p=0.017), receiving information self-perceived as ‘clear and understood’ on cervical cancer (aOR 1.7; 95% CI 1.4 to 2.2, p<0.001), identifying HIV as a risk factor for cervical cancer (aOR 1.4; 95% CI 1.1 to 1.8, p=0.002) and being proposed cervical cancer screening in the HIV clinic (aOR 10.1; 95% CI 7.6 to 13.5, p<0.001), were associated with cervical cancer screening uptake.Conclusion Initiatives to support cervical cancer screening in HIV care programmes resulted in effective access to more than half of the WLHIV in Abidjan. Efforts are still needed to provide universal access to cervical cancer screening, especially among socioeconomically disadvantaged WLHIV.